EFFECT OF ULTRASONIC TREATMENT ON THE CONSOLIDATION OF ODS STEEL FeCrY2O3 PROCESSING WITH CAPSULATED SINTERING PROCESS. - Marzuki Silalahi; Bernardus Bandriyana; Harum Andriadi Bayu; Bambang Sugeng; Rohmad Salam (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2020)
EFFECT OF ULTRASONIC TREATMENT ON THE CONSOLIDATION OF ODS STEEL FeCrY2O3 PROCESSING WITH CAPSULATED SINTERING PROCESS. A new method on the synthesis of ODS (Oxide Dispersion Strengthened) steel for advanced nuclear material was performed by ultrasonic treatment to improve the consolidation process. The raw material of Fe, Cr and Y2O3powder with the composition of Fe-15 wt% Cr, 0.5 wt% and Ytria (Y2O3) as disperzoid were processed by the powder metallurgy method with the main process of pre-alloying, iso-compaction and sintering process. The pre-alloying process was carried out by mixing the alloying elements using ultrasonically treatment at frquency of 20 kHz with variation of 40, 50 and 60 % amplitude. Iso-compaction process was done using the load of 800 psi to obtain a pellet-shaped sample, then continued by the sintering process for consolidation. The sintering process was done in two stages, 1-step sintering and 2-steps sintering, using the heating furnace by putting the sample in a quartz capsule to prevent oxidation attack. Scanning Electron Microscopy-Energy Dispersive X-ray Spectroscopy (SEM-EDS), X-ray Diffraction (XRD), and Micro-hardness tests were carried out to analyze the microstructure and phase formation in relation to the consolidation process. The highest hardness occurred in the addition of treatment with an amplitude of 60% which produces a micro structure with the most fine grain. For 1-step sintering process, the highest hardness of 134.51 VHN obtained at 40 % amplitude. The hardness of the alloy depends on the size of the grain boundary associated with the difficulty of the dislocation movement.